Pattern recognition : 10th Mexican Conference, MCPR 2018, Puebla, Mexico, June 27-30, 2018, Proceedings /: 10th Mexican Conference, MCPR 2018, Puebla, Mexico, June 27-30, 2018, Proceedings. (2018) - Unknown
No abstract available